STRATEGI PEMBINAAN KEPRIBADIAN MUSLIM: STUDI KISAH-KISAH DALAM SURAT AL-KAHFI - DAULAE, TATTA HERAWATI (Institut Agama Islam Negeri Padangsidimpuan, 2015)
The problem of this research is the stories of what is contained in the stories of surah Al-Kahf, and how the strategy of development muslim personality in the stories of surat Al-Kahf. The goal is to find out the stories in the letter of al-Kahf, and the strategy of development personality Muslim in the letter of al-Kahf. This research is library research. This research is library research. The stories contained in the letter of al-Kahf is the story ashab kahfi subsection 9-26, the story of two people who are friends subsection 32-46, the story of Prophet Musa with Khidir subsection 60-82, and the story of Zulkarnaen subsection 83-99. The strategi of development muslim personality in the stories of the letter al-Kahf. In coaching faith that is seeking a jama'ah that faith, strengthen tawakal, the establishment and seeking halal and rizki was clean, the development of mental for exams treasure with instilling a strong faith, to clean of shirk and overbearing, will embed the Day of Judgement, development knowledge with religion and equip science related to life, instill confidence in the wisdom of the fate and the growing of fate the attention, poor, mental coaching for exams power to equip science, mental, physical, raise awareness that the rule would be justified, membelaki sincerity and raise awareness that the success of helping of Allh swt